2007
DOI: 10.1038/nprot.2007.202
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, purification and analysis of histones

Abstract: Histone proteins are the major protein components of chromatin, the physiologically relevant form of the genome (or epigenome) in all eukaryotic cells. Chromatin is the substrate of many biological processes, such as gene regulation and transcription, replication, mitosis and apoptosis. Since histones are extensively post-translationally modified, the identification of these covalent marks on canonical and variant histones is crucial for the understanding of their biological significance. Many different bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
839
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 918 publications
(858 citation statements)
references
References 33 publications
9
839
0
4
Order By: Relevance
“…4A,B. As expected [22,23], H2B had the shortest retention time in the RP-C8 matrix (Fig. 4A,B, upper panels, fractions 91-95 and 93-96 respectively) and the autoradiogram shows no detectable phosphate incorporation in either untreated or cAMPtreated cells (Fig.…”
Section: Hplc Analysis Of Histone Phosphorylation In Metabolically-lasupporting
confidence: 77%
“…4A,B. As expected [22,23], H2B had the shortest retention time in the RP-C8 matrix (Fig. 4A,B, upper panels, fractions 91-95 and 93-96 respectively) and the autoradiogram shows no detectable phosphate incorporation in either untreated or cAMPtreated cells (Fig.…”
Section: Hplc Analysis Of Histone Phosphorylation In Metabolically-lasupporting
confidence: 77%
“…Histones were purified in acidic condition as previously described 45 . Samples were subjected to SDS-PAGE and immunoblotting using standard procedures.…”
Section: Western Blottingmentioning
confidence: 99%
“…The nuclear histones from HeLa cells were isolated using a modified protocol of Shechter et al 27 and established the deacetylation assay using rhHDAC1/rhHDAC6 as controls along with rHos2. In these assays it was found that 0.3 ÎŒg of rhHDAC1 was able to deacetylate the nuclear acetylated histones as detected by an anti-H3-K9 histone antibody.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylated histones were isolated from HeLa cells treated with the HDAC inhibitor SAHA as per published protocol 27 . The histone pellet was then resuspended in ultra pure water, stored in 50 ÎŒl aliquots at -70°C and the protein concentration was determined using a BCA kit (Pierce).…”
Section: Methodsmentioning
confidence: 99%